If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + -9y = 10 Combine like terms: 3y + -9y = -6y -6y = 10 Solving -6y = 10 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '-6'. y = -1.666666667 Simplifying y = -1.666666667
| 5y-3=9+y | | 243/2/3 | | 1+8x^3=0 | | -3x+17=11x+4 | | 3+3m=6 | | 2x+3y+4z=1000 | | 2=x-2m | | xy^2=-10 | | 2/3(y-6) | | 25y^2+13=178 | | 2cos^2+5cosx-3=0 | | 97/2yx2 | | (3ty)(-8t)= | | 7=-x+17 | | -5+2y+3z=-7 | | 2x+4xy+5y+3yx= | | 9=r+8r | | -5y-3=9+y | | 4/10x-4x65=4/5 | | 3(x-5)+4(x+2)=14 | | Y^2+3yx-8x-4z=0 | | -18-4n=-(7+7n)+1 | | -27^-1/3 | | (-27)^-1/3 | | 1/4-(-12/7) | | b(5px-3)=a(qx-4) | | 9y=x-14 | | 189=-v+124 | | k/(-7)=10 | | 6+(8-9p)-2= | | 6y^2-29y+5=0 | | -u+246=159 |